Characterization of lactic acid bacteria recovered from atole agrio, a traditional Mexican fermented beverage. (February 2018) - Väkeväinen, Kati; Valderrama, Anita; Espinosa, Judith; Centurión, Dora; Rizo, Jocelin; Reyes-Duarte, Dolores; Díaz-Ruiz, Gloria; von Wright, Atte; Elizaquível, Patricia; Esquivel, Karina; Simontaival, Anna-Inkeri; Aznar, Rosa; et al.
Abstract: Our aim was to identify and characterize the lactic acid bacteria (LAB) of atole agrio, a fermented Mexican maize-based beverage and to evaluate whether starters could be obtained to produce it under controlled conditions. Atole agrio fermentation process was variable with an abundant presence of Enterobacteriaceae throughout the fermentation. Based on RAPD-PCR, Weissella (29.2%), Pediococcus (24.0%), Lactococcus (17.8%) and Lactobacillus (16.4%) were the most abundant LAB genera. Out of 88 identified LAB strains, 87.5% produced folates, 71.6% degraded phytates, 38.6% produced exopolysaccharides (EPS) and 12.5% had amylolytic activity. The majority of the strains (81.8%) were resistant to at least two of the screened nine antibiotics and 11.4% to one antibiotic. Six potential starters; L. plantarum IL4l1, L. plantarum A1MM10, Lc. lactis IL5l1, Lc. lactis A1MS3, Leuc. pseudomesenteroides IL5l2 and Ped. pentosaceus S0l10, were selected for further studies. All selected strains were phytase producers, showed antimicrobial activity and had good acidification and growth properties. In addition L. plantarum IL4l1, Ped. pentosaceus S0l10 and Leuc. pseudomesenteroides IL5l2 were EPS producers and had together with Lc. lactis IL5l1 amylolytic activity. L. plantarum IL4l1, L. plantarum A1MM10 and Lc. lactis IL5l1 were folate producers. Highlights: The lactic acid microbiota of atole agrio was characterized for the first time. The microbiota of atole agrio was variable between batches. Atole agrio LAB had antimicrobial activity against Enterobacteriaceae. Folate producers and phytate degrading LAB were identified. Promising LAB starters were selected.